PRODUCTION AND HEALTH PARAMETERS IN CATTLE HERDS: A SURVEY FROM EASTERN TURKEY - O. Coban; E. Lacın; N. Sabuncuoglu; M. Genc (Journal of Animal and Plant Sciences, 2013)
In terms of its cattle population Erzurum constitutes a model for cattle management in eastern Turkey. The study was aimed at the assessment of the structure and health conditions of the cattle herds bred in Erzurum province from the perspective of alignment with the relevant European Union acquis. Randomly selected 379 cattle herds and data collected by means of a questionnaire, constituted the material of the study. It was determined that, the mean age of the cattle breeders operating in the province was 44 years old and that the breeders were generally of a low educational profile. The mean number of cattle per herd was 18. In the majority of the herds, no vaccination programme was applied, and it was observed that early postnatal calf mortality reached a level of 16%. Despite the presence of vast pasture areas in Erzurum province, poor pasture quality and low level of roughage production are of major concern. Furthermore, the lack of necessary precautions to protect the health of cattle herds, reduces the production level.
Keywords: Cattle; Management; Herd size; Herd health